Relationships between perceived measures of internal load and wellness status during overseas futsal training camps - Chen, Yung-Sheng; Clemente, Filipe Manuel; Pagaduan, Jeffrey Cayaban; Crowley-McHattan, Zachary J; Lu, Yu-Xian; Chien, Chia-Hua; Bezerra, Pedro; Chiu, Yi-Wen; Kuo, Cheng-Deng (PLoS One, 2022)
Exercise and sport practitioners frequently utilize rating of perceived exertion (RPE) to evaluate the players' psychophysiological strains during training sessions. The subjective rating of physical exertion level during sports training has been shown to have a reciprocal relationship with wellness status during periodic training or competitive seasons. However, the relationship between subjective physical exertions and wellness status during short-term overseas training camps (OTCs) has not been extensively investigated. This study aimed to examine the perceived responses of physical exertions [session-RPE (sRPE), training monotony, and training strain] and wellness status (fatigue, sleep, delayed onset muscle soreness, stress, and mood) measures in elite young adult futsal players from four separate OTCs with different training tasks. Twenty-seven U-20 male national team futsal players voluntarily participated in this study. The players recruited for OTCs were based on their performance during domestic training camps and the tactical demand of the team. The task of each OTCs was defined as: 1) 1st OTC = game-based camp (n = 14); 2) 2nd and 3rd OTC = training-based camp (n = 20 and n = 17, respectively); and 3) 4th OTC = pre-tournament camp (n = 14). The OTCs consisted of 11 training sessions (18.9 hours) and 16 friendly matches (23.8 hours). During daily training sessions and friendly matches, sRPE was used to quantify training load (TL). Additionally, a five-elements general wellness questionnaire was used to evaluate daily wellness status in the morning. The results demonstrated that the mean and sum sRPE in the game-based OTCs were significantly lower compared to the mean sRPE [p < 0.01, effect size (ES) = -4.8; p < 0.01, ES = -2.9] and sum sRPE in the training-based OTCs (p < 0.01, ES = -3.6; p < 0.01, ES = -3.1). The mean (p = 0.01; ES = -2.0) and sum sRPE (p < 0.01; ES = -3.4) in the game-based OTC were also lower than that in the pre-tournament OTC. Conversely, the wellness scores in the game-based OTC were higher compared to the training-based (p = 0.01; ES = 1.8) and the pre-tournament OTCs (p < 0.01; ES = 1.6). There was a negative relationship between mean and sum sRPE and all wellness scores (mean sRPE = r = -0.441 ~ -0.575, p < 0.001; sum sRPE = r = -0.41 ~ -0.559, p < 0.001). Our findings suggested that responses to training sessions, derived from mean and sum sRPE and wellness scores, are dependent upon the task-specific nature of OTCs among elite futsal players. Utilization of mean and sum sRPE and wellness measures to monitor the psychophysiological health during short-term OTCs is recommended.
Keywords: Health Status; fotbal; lidé; únava; cvičení; Female; Exercise; zdravotní stav; Physical Conditioning, Human; Humans; Physical Exertion; kondiční příprava; Fatigue; tělesná námaha; Sports; mužské pohlaví; mladý dospělý; Soccer; ženské pohlaví; Young Adult; Male; sporty